Astrocyte-derived Wnt growth factors are required for endothelial blood-brain barrier maintenance. (April 2021) - Guérit, Sylvaine; Fidan, Elif; Macas, Jadranka; Czupalla, Cathrin Jaqueline; Figueiredo, Ricardo; Vijikumar, Aruvi; Yalcin, Burak Hasan; Thom, Sonja; Winter, Peter; Gerhardt, Holger; Devraj, Kavi; Liebner, Stefan
Highlights: Wnt factor release from astrocytes is crucial for blood-brain barrier maintenance. Loss of astrocytic Wnt release progressively impairs endfoot integrity in ageing. Astrocytic Wnts regulate endothelial caveolin 1 expression and pericyte attachment. Loss of astrocytic Wnt release influences neuronal activation. Abstract: Maintenance of the endothelial blood-brain-barrier (BBB) through Wnt/β-catenin signalling is essential for neuronal function. The cells however, providing Wnt growth factors at the adult neurovascular unit (NVU) are poorly explored. Here we show by conditionally knocking out the evenness interrupted ( Evi ) gene in astrocytes (Evi ΔAC ) that astrocytic Wnt release is crucial for BBB and NVU integrity. Evi ΔAC mice developed brain oedema and increased vascular tracer leakage. While brain vascularization and endothelial junctions were not altered in 10 and 40 week-old mice, endothelial caveolin(Cav)-1-mediated vesicle formation was increased in vivo and in vitro . Moreover, astrocytic end-feet were swollen, and aquaporin-4 distribution was disturbed, coinciding with decreased astrocytic Wnt activity. Vascular permeability correlated with increased neuronal activation by c-fos staining, indicative of altered neuronal function. Astrocyte-derived Wnts thus serve to maintain Wnt/β-catenin activity in endothelia and in astrocytes, thereby controlling Cav-1 expression, vesicular abundance, and end-feet integrity at the NVU.